Modification of coal fly ash for high capacity adsorption of methylene blue - Mardiyah Kurniasih; Nurul Hidayat Aprilita; Roto Roto; Mudasir Mudasir (Case Studies in Chemical and Environmental Engineering)
Coal fly ash (FA) waste from local thermal power plant has been modified by acid activation and SiO2 enrichment using hydrochloric and acetic acids. The modified FA with acid activation (FAA_HAc and FAA_HCl) and SiO2 enrichment (SiO2_HCl and SiO2_HAc) were applied in the adsorption of methylene blue (MB) from aqueous solution. The physicochemical and morphological characteristics of the modified FA were characterized by XRF, SEM-EDX, XRD, BET, and TGA. The adsorption study was carried out in a batch system by optimizing pH, adsorbent dosage, contact time, initial dye concentration and temperature. The optimum adsorption is achieved at pH 8.0, adsorbent dosage of 1.5 g/L and contact time of 75 min. The experimental data fits the pseudo-second-order models and the activation energies (Ea) are 48.71, 48.95, 32.26, and 30.61 kJ mol−1 for FAA_HAc, FAA_HCl, SiO2_HAc, and SiO2_HCl, respectively. Langmuir, Freundlich, or Temkin isotherm models described well the experimental data. The maximum adsorption capacities (qm) of FAA_HAc, FAA_HCl, SiO2_HAc, and SiO2_HCl with Lamgmuir model at 318 K are 151.33, 146.18, 100.78, and 95.81 mg/g, respectively. The qm values increase with temperature, indicating endothermic adsorption process. Themodynamic study gives the positive value of enthalpy (ΔH°) and entropy (ΔS°), and the negative value of free energy (ΔG°) changes, suggesting an endothermic and spontaneous process. The lower activation energy and higher adsorption capacity of modified FA with a simple, low-cost and eco-friendly technique provide a prospective application of the adsorbents for the removal of dye waste from aqueous solution.